Rethinking the participatory paradigm in plant breeding: A nombreeder's perspective - Upreti, Bishnu Raj (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper attempts to highlight the fact that it is time to criticality rethink the use of the participatory paradigm in research and development. The notion of participation is not only highly debated but also heavily misused and abused in research and development discourses. Rhetorically, almost all documents Of government, research organizations, NGOs, and NGOs impressively use such terms as beneficiaries' Participation, participatory approach, use of indigenous knowledge, bottom-up planning, etc. But in reality, they themselves control the participatory process by imposing their criteria, conditions, and regulations. The global as well as Nepalese experiences in participatory approaches in both research and Development show that the commitment and confidence of local people is not gained at the desired level. The participation of beneficiaries in the research and development process is not only a means but also an end that empowers people. Participation has to focus on contributing, influencing, sharing, and redistributing power, resources, benefits, and knowledge. Therefore, the essence of the participatory process lies in helping people to make their own decisions and to take responsibility for their own welfare this perspective has profound implications for choosing approaches and methodologies for participatory plant breeding. New challenges in plant breeding are posed by genetic engineering, biotechnology, globalization, patenting, and a profit-oriented focus. Three is increasing evidence that scientists have a strong egocentric involvement in their innovations, which is often in conflict with the tremendous knowledge and experience of local people. Hence, it is lime to rethink the participatory paradigm in research and development and develop new professionalism to address the newly emerging challenges.